THE QUALITY OF STUDENT WORKSHEETS (LKPD) ON WRITING DESCRIPTION TEXT THROUGH FISHBONE DIAGRAM STRATEGY - Rahmi Ulfi; Charlina Charlina; Elvrin Septyanti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
Research on the Quality of Student Worksheets (LKPD) using the fishbone diagram strategy aimed to determine the quality of the product in the form of Student Worksheets which were used as teaching material media to help students in developing writing. For this reason, students tended not to have difficulties when learning the writing descriptive text skills. This LKPD used fishbone diagram strategy that resembled a fishbone used in speaking and writing skills. This research was a research and development (R&D). The data analysis technique was quantitative description. The results showed that Student Worksheet writing descriptive text using the fishbone diagram strategy was feasible to be used as a companion to teaching materials. The validation results from material experts stated that LKPD obtained a percentage of 97.6% and 91.7%, while the validation from linguists achieved feasibility with a percentage of 88% and 86%. The feasibility test for field experts (teachers) got a percentage of 93.68% and 94.73% and the trials on grade VII students of SMP Negeri 1 Kota Dumai were obtained with a percentage of 84.62%.